Comparison of Cardiac Wall Thicknesses and Coronary Artery Obstructions Between Deaths Resulting From Acute Myocardial Infarction and Deaths From Other Causes - Ismail ALTIN; Mucahit ORUC; Osman CELBIS; Emine TURKMEN SAMDANCI (Medeniyet Medical Journal)
Objective: The risk factors for myocardial infarction (MI) can be separated into three general categories: non-modifiable factors, modifiable risk factors, and lifestyle. This study aimed to investigate whether or not there was any effect of cardiac wall thickness and coronary artery obstructions on acute MI. Methods: In this retrospective study of histopathological examinations of autopsies, two groups were formed. The first contained 28 cases diagnosed with acute MI and the second 28 cases with no heart pathology and the cause of death was reasons other than heart disease. The subjects in the two groups were similar in age, height, weight, and body mass index. The groups were compared in terms of the left and right ventricular wall thicknesses and the degree of obstruction of the right, left, anterior descending, and circumflex coronary arteries. Results: The mean left ventricular wall thickness was 1.461+-0.2767 cm in the acute MI group and 1.386+-0.2460 cm in the control group, with no statistically significant difference found between the two groups (p=0.289). A statistically significant difference in the degree of obstruction of the coronary arteries was found between the groups. Conclusions: Although the mean cardiac wall thickness was greater in the acute MI cases, no statistically significant difference was found between the two groups.